Study of socio economic status impact and success factors of 1 Azam Niaga participants of Sarawak Economic Development Corporation / Andy Drahman, Mohd Uzairi Ahmad Hajazi - Drahman, Andy; Ahmad Hajazi, Mohd Uzairi (Universiti Teknologi Mara Cawangan Sarawak kampus Samarahan, 2013)
This paper aims to evaluate and assess the impact of 1AZAM Niaga, one of initiatives under Government Tranformation Programme (GTP) that is being carried out by Sarawak Economic Development Corporation (SEDC). As there is no research yet to study the impact and success factor of participants of this program, we attempt to provide academically sound analysis on the impact of 1AZAM Niaga towards the low income households target group, determine the factor behind the success of its participants, and also to give recommendation for further improvement. Using input gathered from the participant of the programme and data from SEDC, improvements of livelihood of participants and factors contributing to the success of participants is analyzed. Through descriptive analysis, it is found that the programme has improved income of the participant and it is significantly correlated with perception towards their improvement. Furthermore, through principal component analysis and binary logistic regression analysis, it is found that "Entrepreneurial Characteristic" and "Entrepreneurial Environment" are significantly contributing to the possibility of participant in agreeing that the programme has improved their livelihood, i.e. increasing the possibility of success of 1AZAM Niaga participant. However, it also found that none of demographic characteristic of participants have significant contribution to their success in this programme.